KOMISARIS INDEPENDEN, KEPEMILIKAN MANAJERIAL, KUALITAS AUDIT, UKURAN PERUSAHAAN DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Dea Nadiya Damayanti; Dadang Suhendar; Lia Dwi Martika (Jurnal Riset Keuangan dan Akuntansi, 2023)
This study aims to determine the effect of independent commissioners, managerial ownership, audit quality, firm size and leverage on the integrity of financial statements. The sample in this study is the mining sector companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique used is non-probability sampling. The sample method uses quota sampling. The data analysis technique using software analysis eviews-9. The test results from the proposed hypothesis show that independent commissioners, managerial ownership, audit quality, firm size and leverage have a joint effect. the same to the integrity of financial statements. The results of the partial study show that independent commissioners and leverage have a significant negative effect on the integrity of financial statements. Managerial ownership, audit quality and firm size has a significant positive effect on the integrity of financial statements. Keywords: Integrity of Financial Statements, Independent Commissioner, Managerial Ownership, Audit Quality, Company Size, Leverage